Reservoir 1D heat transport model. Issue 2 (3rd April 2019) - Polli, Bruna Arcie; Bleninger, Tobias
Abstract : Thermal stratification in lakes, hydropower or drinking water reservoirs occurs mainly by the effect of temperature on water density. One-dimensional heat transport models are widely used to simulate vertical temperature profiles since vertical temperature gradients are dominant in reservoirs. Many applications have been made using one-dimensional models, however, there are still features to be improved to reproduce physical processes or allow for better data analysis. The article describes an unsteady one-dimensional heat transport model with high spatial and temporal resolution, including an energy conservation analysis of three numerical schemes: explicit and implicit finite difference and implicit finite volume methods. It is also simulated thermal diffusivity related to advection for run-of-river reservoirs. An application of the one-dimensional heat transport model (MTCR-1) is performed in Vossoroca reservoir (located near to Curitiba, Brazil), comparison with measured data and characterization of the mixing and stratification periods using physical indices are presented.